Experimental and numerical investigations on the axial capacity of cold-formed steel built-up box sections. (September 2019) - Roy, Krishanu; Ting, Tina Chui Huon; Lau, Hieng Ho; Lim, James B.P.
Abstract: Built-up box sections are becoming increasingly popular for column members in cold-formed steel (CFS) construction; uses of such sections include CFS trusses, space frames, and portal frames. In this article, the built-up box sections are formed through two identical lipped channels connected at their flanges with self-drilling screws. In such an arrangement, independent buckling of the individual channels is prevented by the screws. This paper presents an experimental investigation on axial capacity of built-up CFS box sections. Tests were conducted for different values of slenderness from short to slender columns. In total, the results from 16 experimental tests are reported. Of these, 8 tests were conducted on built-up CFS box sections and the remaining 8 tests were conducted on single channel sections. Load-axial shortening relationship, and failure modes are discussed for built-up columns. Nonlinear finite element (FE) models were developed for built-up CFS box sections and single channels. FE models considered material nonlinearities, initial imperfections and modeling of intermediate fasteners. FE results showed good agreement against the test results. A parametric study was conducted which comprises 148 models to investigate the effect of fastener spacing on axial capacity of built-up CFS box sections. Both FE and test results were compared against the design strengths calculated in accordance with the American Iron and Steel Institute (AISI) and Australian and New Zealand Standards (AS/NZS). From the comparison, it was observed that the AISI & AS/NZS are conservative by around 17% while determining the axial capacity of such built-up CFS box columns. Highlights: Experimental tests were conducted on CFS built-up box sections under axial compression. Results from an experimental regime and elasto-plastic finite element are reported. Local and overall imperfections are considered in FE models The validated FE model was used for a parametric study to investigate the effect of screw spacing. The design strengths in accordance with the AISI & AS/NZS are conservative by around 17% for CFS built-up box columns